2005
DOI: 10.1097/00130404-200511000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic Aspects of Aging

Abstract: A gradual diminution in the physiologic reserve or functional capacity over time is the characteristic hallmark of aging, and this has a direct impact on the choice of cancer therapy and its toxicity profile in elderly patients with cancer. With the expected rapid rise of the older population as a subgroup, oncologists will increasingly treat elderly patients. Provision of competent care to this increasing pool of older patients with cancer necessitates that oncology professionals become familiar with age-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(47 citation statements)
references
References 112 publications
1
44
0
2
Order By: Relevance
“…A gradual decline in physiologic reserve of all tissues and organ systems is a hallmark of aging and many chronic diseases [43, 44]. Chemotherapy has the potential to rapidly accelerate this decline.…”
Section: Methodsmentioning
confidence: 99%
“…A gradual decline in physiologic reserve of all tissues and organ systems is a hallmark of aging and many chronic diseases [43, 44]. Chemotherapy has the potential to rapidly accelerate this decline.…”
Section: Methodsmentioning
confidence: 99%
“…17,19,20 The degree and timeline of this decline vary among different individuals and organ systems. Although these changes are generally imperceptible over the years, they can be unmasked through various internal and external stressors.…”
Section: Physiologic Changes That Occur With Agingmentioning
confidence: 99%
“…17,19,20,25,26 Moreover, there is a decreased response to catecholamines with stress. 25,26 Depending upon obesity, heredity factors, nutrition, weight loss, diet, and racial differences, such changes may be increasingly accentuated over time.…”
Section: Physiologic Changes That Occur With Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that overall health is more predictive for chemotherapy tolerance than chronologic age. 6-10 Although decreased organ function is experienced universally with aging, 11,12 the rate and degree of decline differs from person to person as a result of unique genetic and environmental factors. The standard oncology workup provides vital information to guide management of all patients with cancer, but it is not sufficient to identify those who are more vulnerable to treatment complications.…”
Section: Going Beyond Chronologic Agementioning
confidence: 99%